Report of the 33rd annual conference held in the White Rock Pavilion, Hastings, October 2nd to 6th, 1933. - Labour Party (London : Labour Party, 1933)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Groot-Brittannië.